1997
DOI: 10.1002/(sici)1097-4628(19971017)66:3<499::aid-app10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Superabsorbent polymeric materials. IV. Swelling behavior of crosslinked poly [sodium acrylate-co-N,N-dimethyl (acrylamidopropyl) ammonium propane sulfonate] in aqueous salt solution

Abstract: A series of xerogels based on sodium acrylate (SA), N,N-dimethyl(acrylamidopropyl) ammonium propane sulfonate (DMAAPS), and N,N-methylene bisacrylamide (NMBA) were prepared by inverse suspension polymerization. The water absorbency or swelling behavior for these xerogels in water or various saline solutions was investigated. Results obtained from this study revealed a water absorbency of 721 g H 2 O/g sample in deionized water and 83 g H 2 O/g sample in 0.9 wt % NaCl solution for a gel containing a 1.50 1 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
5
12
2
Order By: Relevance
“…Because the water absorbency was primarily attributed to the water absorbed by the gels and the free water residing between the gel particles, the smaller absorbency by suction was primarily due to the scarcity of free water between the gel particles. Similar phenomena were observed in some of our previous studies,30, 31, 38, 39 but a contrary result was found in our previous study on NaA–HEMA copolymeric gel series 29. This was due to the higher molar ratio of HEMA, over 1.5 × 10 −2 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Because the water absorbency was primarily attributed to the water absorbed by the gels and the free water residing between the gel particles, the smaller absorbency by suction was primarily due to the scarcity of free water between the gel particles. Similar phenomena were observed in some of our previous studies,30, 31, 38, 39 but a contrary result was found in our previous study on NaA–HEMA copolymeric gel series 29. This was due to the higher molar ratio of HEMA, over 1.5 × 10 −2 .…”
Section: Resultssupporting
confidence: 82%
“…Superabsorbents based on acrylic acid (AA) have been extensively studied because AA is cheap and easily polymerized into a high‐molecular‐weight polymer. In previous investigations, we studied the swelling behavior of a series of superabsorbents in deionized water and various saline solutions, such as the poly(sodium acrylate) [poly(NaA)]‐containing nonionic comonomer 2‐hydroxyethyl methacrylate (HEMA),29 the zwitterionic monomer 3,3‐dimethyl methacryloyloxyethyl ammonium propane sulfonate,30 3,3‐dimethyl acrylamidopropyl ammonium propane sulfonate,31 the anionic monomer sodium 2‐acrylamido‐2‐methyl propane sulfonate,32 the cationic monomer trimethyl methacrylamido propyl ammonium iodide,33 and poly(NaA) with various initial total monomer concentrations 34…”
Section: Introductionmentioning
confidence: 99%
“…This occurrence makes the hydration ability become stronger, and the water absorbency increases. Similar results were observed from our previous reports [27][28][29][30][31] and conform to the formation constant of complexation.…”
Section: Water Absorbency In Various Salt Solutionssupporting
confidence: 93%
“…A series of superabsorbent polymers, for study of swelling behavior in deionized water and various saline solutions, were reported in our previous articles, such as poly(SA) containing nonionic comonomer 2-hydroxyethyl methacrylate (HEMA), 26 zwitterionic monomer 3,3-dimethyl methacryloyloxyethyl ammonium propane sulfonate (DMAPS), 27 3,3-dimethyl acrylamidopropyl ammonium propane sulfonate (DMAAPS), 28 anionic monomer sodium 2-acrylamido-2-methyl propane sulfonate (NaAMPS), 29 poly(SA) with various initial total monomer concentrations. 30 According to our previous studies, the SA gels containing nonionic comonomer HEMA had reduced water absorbency but improved initial absorption rate.…”
Section: Introductionmentioning
confidence: 99%
“…Ogawa et al studied the kinetics of the swelling of poly(SA) [poly(sodium acrylate)] using picture analysis with a microscope–VTR system, calorimetry, and gravimetry techniques. We previously reported the swelling behaviors in water and in various saline solutions of a series of superabsorbent polymers,26–30 including SA copolymerized with the nonionic comonomer 2‐hydroxyethyl methacrylate (HEMA),26 with the zwitterionic monomer 3,3‐dimethyl methacryloyloxyethyl ammonium propane sulfonate (DMAPS),27 with 3,3‐dimethyl acrylamidopropyl ammonium propane sulfonate (DMAAPS),28 and with the anionic monomer sodium 2‐acrylamido‐2‐methyl propane sulfonate (NaAMPS) 29…”
Section: Introductionmentioning
confidence: 99%